Exploratory Factor Analysis of Online Teaching Effectiveness in Nursing Education - Catabona, Zuzette Basa (Proceedings Series on Health & Medical Sciences, 2025)
The rapid growth of online education has necessitated an in-depth investigation into the factors influencing teaching effectiveness in online learning environments. This study aims to identify and examine the key factors contributing to the online teaching effectiveness of nurse instructors through Exploratory Factor Analysis (EFA) and develop a tool to measure the Online Teaching Effectiveness (OTE) of nursing instructors. Preliminary item statements were developed based on a thorough review of relevant literature, resulting in a 49-item scale. A multidisciplinary panel member then validated the content, reducing it to a 48-item Content Validated item statement. Pilot testing with 596 third-level students from the College of Nursing at NEUST led to a final set of 41 items. The EFA in this study was carried out using a single random subsample of 410 Level IV Bachelor of Science in Nursing (BSN) student nurses from Higher Education Institutions across Luzon, Visayas, and Mindanao in the Philippines. All respondents were enrolled in the BSN program and participated in online education. This sample size adhered to the "10-times rule," ensuring at least ten observations per variable for the Exploratory Factor Analysis (EFA). Using the five-step Exploratory Factor Analysis Protocol (preliminary analysis for evaluation of data suitability for EFA, factor extraction, factor retention, and factor rotation) determines the data suitability for Exploratory Factor Analysis. This process, employing Varimax and Kaiser Normalization, revealed a 3-factor structure: (1) Active Learning, (2) Instructor-Learner Connection, and (3) Modern Teaching, comprising 28-item statements. Together, these factors explained 75.221% of the variance. The 75.221% variance explained by the three factors is a relatively high value, suggesting that the model provides a good fit to the data. The findings can guide instructional practices by highlighting the importance of active learning, strong instructor-student relationships, and the use of modern teaching techniques. By understanding these factors, educators can make informed decisions to improve their instructional practices and enhance student success. While these findings shed light on online teaching effectiveness in nursing education, further psychometric validation is needed to refine the instrument. Future research should explore its applicability across different samples and disciplines to better evaluate online teaching quality.